(untitled) (Research, Society and Development, 2021)
Playful games are useful methodologies for teaching-learning processes, as they are characterized as alternatives that help students build knowledge. Games and games are gaining space and importance in all approaches related to childhood. The playful activity, which can be expressed in the game, in the toy or play, is of fundamental importance in school education and in the training of man. It allows the educator to perceive traits of the student’s personality and behavior, which facilitates the planning of pedagogical strategies in the ludic environment, promoting motivation for better learning. The objective of the work was to carry out an integrative review in bibliographic platforms to obtain results of the effectiveness of the use of educational games in the school environment, also to seek the importance of the use of educational games to help the teaching professional and to identify the students’ learning through educational games. In the results of the review, 9 publications were found over a 10-year period from 2010 to 2020. The publications address how playful activity is essential in the school environment and how teachers need more resources and motivation by the school to better apply it.